Impact of using XP-endo finisher and nanobubble water during EDTA dentin conditioning on TGF-β1 release in regenerative endodontic procedures - Mai Sayed Hanafy; Ahmed Khaled Abdella Ahmed; Rana Gehad Salem (BMC, 2024)
Abstract Introduction Transforming Growth Factor-Beta 1 (TGF-β1) plays a crucial role in the success of Regenerative Endodontic Procedures (REPs) as they directly impact the proliferation and differentiation of stem cells. TGF-β1 is released by conditioning of the dentin matrix using 17% EDTA. EDTA was found to have deleterious effects on dentin especially in immature teeth with fragile dentin walls. Decreasing the irrigation time was reported to decrease these effects. Accordingly, enhancement and activation of the EDTA solution to maintain its efficiency in TGF-β1 release from dentin and thus compensating the reduction in irrigation time was employed. EDTA solution was enhanced by adding Nanobubble (NB) water which contains oxygen filled cavities less than 200 nm in diameter. Additionally, EDTA was activated with XP-endo Finisher rotary file. The aim of this study was to assess the impact of NB enhancement and/or XP-endo Finisher activation of the EDTA solution on the TGF-β1 release from dentin. Methods Fifty standardized root segments with open apex were allocated to two main groups according to whether EDTA was enhanced with NB water or not, and within each group whether XP-endo Finisher activation was used or not in addition to a Negative Control group. The concentration of the released TGF-β1 in the root canal was measured using enzyme-linked immunosorbent assay (ELISA). The statistical analysis was done using the Shapiro- Wilk, Kolmogorov Smirnov, ANOVA and Post-hoc Tukey tests. Results All groups released a considerable amount of TGF-β1 with the highest values in the EDTA/NB/XP group, followed by EDTA/NB, EDTA/DW/XP, EDTA/DW and Negative Control groups respectively. Conclusions The results of this study suggest that NBs can promote the success of REPs since it revealed a significant increase in the TGF-β1 release following its use in the enhancement of the EDTA solution. A comparable effect was obtained by XP-endo finisher activation of the EDTA solution. The combined use of NBs and XP-endo Finisher can be a promising addition in REPs. Accordingly, Enhancement and activation of the EDTA solution may compensate decreasing the EDTA irrigation time attempted to avoid the deleterious effect of EDTA on dentin.